(untitled) (Nusantara Medical Science Journal, 2025)
Introduction: The global prevalence of obesity among women of reproductive age has increased markedly over the past two decades, reaching 24% in high-income and 16% in low- and middle-income countries. This trend contributes to adverse maternal and neonatal outcomes, including a 2–4-fold higher risk of gestational diabetes, a threefold increase in preeclampsia, and up to a 50% higher caesarean delivery rate. Maternal metabolic disorders also have long-term consequences for offspring metabolic and cardiovascular health. Objective: To synthesize current biological and epidemiological evidence linking maternal metabolic status to offspring health within the Developmental Origins of Health and Disease (DOHaD) framework. Methods: A comprehensive search was conducted in PubMed, Scopus, and Web of Science from January 2015 to September 2025 using keywords related to maternal obesity, metabolic syndrome, DOHaD, offspring health, and epigenetics. Included studies comprised human and animal research with follow-up beyond two years, while case reports, editorials, and studies without long-term outcomes were excluded. Findings: From 22 eligible studies, consistent evidence indicates that maternal obesity and metabolic syndrome affect offspring through placental dysfunction, systemic inflammation, and epigenetic reprogramming. Offspring of obese mothers show a 1.5–2.8-fold increased risk of obesity and insulin resistance during adolescence and adulthood. Epigenome-wide analyses reveal altered methylation of genes regulating lipid metabolism (LEP, IGF2) and inflammatory pathways, supporting the DOHaD hypothesis. Conclusion: Maternal metabolic health critically shapes offspring developmental and metabolic outcomes. Preconception and antenatal interventions targeting metabolic optimization provide key opportunities to prevent intergenerational transmission of metabolic risk and promote healthier future generations.